Rural road management and socioeconomic development in a district of San Ignacio, Perú (2023)
The research focuses on determining the relationship between Rural Road Management (GVR) and socioeconomic development in a district of the province of San Ignacio, Peru. A quantitative approach is used, basic type, non-experimental design and simple correlation. The sample was made up of 52 employees of the municipal entity, using the survey as a technique to collect the information. 75% of respondents consider the level of GVR to be high, while 71.2% consider socioeconomic development to be medium level. Furthermore, the GVR and socioeconomic development variables have a high positive correlation, with their Rho Spearman coefficient being 0.783 and a bilateral significance level of 0.000, with a p value below 0.05. This implies that with greater GVR, socioeconomic development will also be greater, which was identified in the analysis of the context and the characterization of the problematic situation.